Factors Predicting Testing and Treatment of Iron Deficiency in a Nationwide Cohort of Anemic UC Patients. Issue 12 (December 2016) - Khan, Nabeel; Patel, Dhruvan; Shah, Yash; Yang, Yu-Xiao
Abstract : Background: Iron deficiency anemia (IDA) is an often unrecognized and undertreated complication of ulcerative colitis (UC). We conducted the first nationwide study in the United States to evaluate the prevalence of testing for iron deficiency (ID) in anemic UC patients and determine the frequency of treatment with iron supplementation in patients with IDA. Methods: Nationwide cohort of patients with newly diagnosed UC in the Veterans Affairs health care system was identified. Primary outcome was to evaluate if anemic UC patients were tested for ID and subsequently treated with iron replacement therapy if IDA is confirmed. Candidate parameters included factors that can impact testing and treatment of anemia including patients' demographics, severity of anemia, and endoscopic findings. Results: Of 836 newly diagnosed patients with UC, 585 patients (70%) developed anemia over the course of median 8 years of follow-up. Of 585 patients, 401 patients (68.6%) had iron study evaluation. Two hundred fifty-one patients (62.6%) were diagnosed with IDA, and among them, 191 patients (76.1%) were treated with oral iron therapy. None of the patient received intravenous iron therapy. In multivariate analysis, patients with mild/moderate anemia and patients from Midwest and South region were independent predictors of iron study evaluation in patients with anemia. Conclusions: More than a third of anemic UC patients were not tested for ID. Once tested, almost a quarter of the patients with IDA were not treated with iron replacement therapy. Testing for ID and subsequent treatment with iron replacement therapy should be considered among the quality process indicators in UC. Abstract : Article first published online 18 October 2016.